Doing Psychological Research / Gathering and Analysing Data - Hayes Nicky (Open University Press, 2000)
This book has been carefully written and designed in order to help you understand psychological research methods and develop the skills you need to carry out your own research projects. Introduction, Approaches to Psychological Research, Gathering Data, Gathering Data for Psychological Research, Experiments, Observational Studies, Questionnaire Studies, Psychometrics, Interviews, Case Studies and Ethnography, Analyzing Documents, Making Sense of Data, Introducing Qualitative Analysis, Grounded Approaches to Qualitative Research, Conservations and Discourse and Images, Protocol Analysis and Other Techniques, Introducing Quantitative Analysis, Numbers as Descriptive Statistics, Descriptive Statistics in Visual Image, Two-Sample Tests, Correlation and Regression, Analysis of Variance, Glossary, Statistical Tables, References, Index.